Evaluating the Association between Keratoconus and Reported Genetic Loci in a Han Chinese Population. (June 2015) - Hao, Xiao-Dan; Chen, Peng; Chen, Zhao-Li; Li, Su-Xia; Wang, Ye
ABSTRACT Background: Keratoconus (KC) is a complex degenerative disorder of the cornea. Genetic, environmental, and lifestyle factors may all contribute to the pathogenesis of KC. Most of the reported KC-associated SNPs have been detected in Caucasians and Australians. To investigate whether the reported associated SNPs can be found in a Chinese population, we performed a replication study of the significantly associated SNPs. Materials and Methods: A total of 210 unrelated Chinese KC patients and 191 unrelated controls were included in the present study. SNPs rs4954218 (Near RAB3GAP1 (5′)), rs4894535 (FNDC3B), rs2956540 (LOX), rs3735520 (Near HGF (5′)), rs1324183 (MPDZ-NF1B), rs1536482 (RXRA-COL5A1), rs7044529 (COL5A1), rs2721051 (Near FOXO1 (3′)), rs9938149 (BANP-ZNF469) and rs6050307 (VSX1) were assessed for their association with KC. The genotype of each SNP was detected using the Sequenom MassARRAY-Assay. Results: SNP rs1324183 located in MPDZ-NF1B was associated with an increased risk of KC (OR = 3.108, 95% CI = 1.366–7.072, p = 0.005), and SNP rs2956540 in the LOX gene may confer a reduced risk of KC with a borderline p value in our population (OR = 0.664, 95% CI = 0.447–0.986, p = 0.042). No significant difference was observed between patients and controls in the other eight SNP genotypes and allele frequencies. Conclusions: The replication association of rs1324183 (MPDZ-NF1B) with KC in our population and the results, which are identical to those in different populations, suggest that rs1324183 (MPDZ-NF1B) is a common genetic risk for KC and should be further investigated.